PELATIHAN DAN PENDAMPINGAN PEMASARAN PRODUK URBAN FARMING DI KELURAHAN PANDANWANGI KOTA MALANG - Relawati, Rahayu; Ariadi, Bambang Yudi; Shodiq, Wahid Muhammad (Kumawula: Jurnal Pengabdian Kepada Masyarakat, 2025)
The Urban Farming Group in Pandanwangi Village, Malang City, produces both agricultural and processed products, however, their marketing is still limited in the local area. This community service program aims to provide training and marketing assistance to expand market reach and increase the income of group members. The procedure of the activity is carried out by training and mentoring methods. The target participants of this program are members of the Urban Farming group in Pandanwangi Village, Malang City. The training covered  product marketing materials, namely direct marketing and digital (online) marketing. The implementation of the next mentoring is focused on digital marketing. Intensive mentoring was conducted  for two months in collaboration with students participating in the PMM (Community Service by Students) program. The results of the activity indicate that the training and mentoring carried out are able to open up broader marketing insights and show great digital marketing potential. The target participants were highly engaged and cooperative during the mentoring process, leading to the creation of a joint platform accessible to all Urban Farming Working Groups. Further community service activities are needed to maintain the sustainability and development of digital marketing, increase viewers and transactions in digital marketing of Urban Farming products. Kelompok Urban Farming di Kelurahan Pandanwangi Kota Malang memiliki produk-produk pertanian dan olahan produk, namun pemasaran masih terbatas di wilayah setempat. Kegiatan pengabdian bertujuan memberikan pelatihan dan pendampingan pemasaran agar lebih luas dan pendapatan anggota kelompok bisa meningkat. Prosedur kegiatan dilakukan dengan metode pelatihan dan pendampingan. Sasaran kegiatan adalah anggota kelompok Urban Farming di Kelurahan Pandanwangi, Kota Malang. Pelatihan diberikan dengan materi pemasaran produk, yakni pemasaran langsung dan pemasaran digital (online). Pelaksanaan pendampingan selanjutnya difokuskan pada pemasaran digital. Pelaksanaan pendampingan secara intensif selama dua bulan dikolaborasikan dengan mahasiswa peserta PMM (Pengabdian Masyarakat oleh Mahasiswa). Hasil kegiatan menunjukkan bahwa pelatihan dan pendampingan yang dilakukan mampu membuka wawasan pemasaran yang lebih luas dan menunjukkan potensi digital marketing yang besar. Mitra sasaran sangat aktif dan kooperatif selama pendampingan hingga terbentuk platform bersama yang dapat dimanfaatkan oleh seluruh Pokja Urban Farming. Kegiatan pengabdian selanjutnya diperlukan untuk menjaga keberlanjutan dan pengembangan pemasaran digital, peningkatan viewer dan transaksi pada pemasaran digital produk urban farming.